THE WORLD CHALLENGE OF ISLAMIC EDUCATION TOWARD HUMAN RESOURCES DEVELOPMENT - Ashari, Riza; Syam, Aldo Redo; Budiman, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The problem of human resources is still a focus and a spell for Islamic educational institutions to survive in this era of globalization. Human resources have a major role in every activity of Islamic educational institutions. Although supported by facilities and infrastructure and excessive sources of funds, but without the support of reliable human resources activities of Islamic education institutions will not be resolved properly. So, the quality human resources development in Islamic education is needed in Islamic educational institutions to a better direction. And the development needs top management support as an important first step to do not just lip service. Leaders should be able to mobilize the development of human resources of Islamic education in their institutions. Human resources development in Islamic education can affect organizational performance by using human resource expertise related to management practices and targets are broad, not only limited to operational human resources, but also includes managerial level. So it is not wrong if the challenge of education at this time lies in the aspect of human resource development of Islamic education, whereas if done well, this development will provide an essential value to support the success of Islamic education institutions, especially in the current era of globalization.